To the question of academic activity of students at the self-studying of the sections of the course of higher mathematics - Irina N. Pavlova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In the age of developed information technologies and taking into account the requirements of Federal State Educational Standards, the development and implementation of electronic methodological complexes is particularly relevant. In order to improve the effectiveness of out-of-class independent work of students in preparing for classes and various kinds of control (exam, test, intermediate control tests, etc.), the section "learners" was created on the website of the department of VM and PI. The article reviews and analyzes the statistical analysis of the attendance of the site VM and PI as a result of activation of independent work of students.